Stylized Line Drawing and Shading Effects for Cartoon Rendering (International Journal of Innovative Computing, 2016)
Due to increasing demands of cartoon style in many areas of computer graphic aspects, this paper presents a simple stylized shading technique to enhance the cartoonish appearance in two aspects. First, a new toon-illumination model is developed to emphasize the boundaries between diffuse reflection part and specular reflection part in the phong illumination model. The new discrete shading will be exploited to convey the light and dark orientations on the surface of 3D model. Second, we combine stylized lines with non-photorealistic shading effect to convey more visual cues of tone. The experimental result reveals the ability of proposed model to produce many cartoon effects.